Purified glucocorticoid receptors bind selectively in vitro to a cloned DNA fragment that mediates a delayed secondary response to glucocorticoids in vivo. - Hess, P (1990)
We have identified and characterized a 206-base-pair region downstream from rat alpha 2u-globulin promoter that specifically mediates a delayed secondary response to glucocorticoids. Unlike positive primary glucocorticoid response elements (GREs), this regulatory element, termed delayed sGRE, dictates an inductive process preceded by a time lag of several hours and blocked by the protein synthesis inhibitor cycloheximide. Reminiscent of GREs and negative GREs (nGREs), a delayed sGRE confers hormonal regulation upon a linked heterologous promoter from a downstream position with respect to transcription start site and, remarkably, also interacts selectively with purified glucocorticoid receptor. These results imply that receptor binding to a delayed sGRE in vivo may mediate certain secondary responses to glucocorticoid hormones.